A 9‐year‐old girl with blisters on the hands and face: An early presentation of variegate porphyria. Issue 2 (30th September 2022) - Moshayedi, Aref; Mochel, Mark C.; Brooks, Amy N.; Laver, Joseph; Salkey, Kimberly S.
Abstract: Variegate porphyria (VP) is a rare subtype of porphyrias characterized by dysfunction of enzymes in the heme biosynthesis pathway leading to an accumulation of porphyrins and their precursors. The resulting buildup can manifest as neuropsychiatric symptoms and photosensitive blistering eruptions on sun‐exposed skin. We report a case of VP in a 9‐year‐old girl with many confounding medical factors that warranted alternative explanations for her cutaneous lesions. VP has been reported infrequently in the pediatric population and is associated with more severe neuropsychiatric outcomes compared to adult‐onset disease.